Molecular characterization and evolution of a chemosensory receptor gene family in three notorious rice planthoppers, Nilaparvata lugens, Sogatella furcifera and Laodelphax striatellus, based on genome and transcriptome analyses. Issue 9 (30th April 2018) - He, Peng; Engsontia, Patamarerk; Chen, Guang‐Lei; Yin, Qian; Wang, Jun; Lu, Xu; Zhang, Ya‐Nan; Li, Zhao‐Qun; He, Ming
Abstract : Conserved odorant co‐receptor ( Orco ) genes are closely related to insect olfaction. Knockdown Orco rice planthoppers lose much of their olfactory ability and fail to seek out rice plants. Abstract: BACKGROUND: The white‐backed planthopper (WBPH) Sogatella furcifera, the brown planthopper (BPH) Nilaparvata lugens, and the small brown planthopper (SBPH) Laodelphax striatellus (Hemiptera: Delphacidae) are rice pests that damage rice plants by sap‐sucking and by transmitting viruses. Host‐seeking behavior involves chemosensory receptor genes that include odorant receptors (ORs), ionotropic receptors (IRs) and gustatory receptors (GRs). RESULTS: We used genome and transcriptome data to identify 141 ORs, 28 GRs and 25 IRs in BPH; 135 ORs, 18 GRs and 16 IRs in WBPH; and 37 ORs, 14 GRs and 6 IRs in SBPH. A phylogenetic analysis identified several specific OR clades of rice planthoppers, the results indicating that these OR members might be used to respond to specific host volatiles. OR co‐receptor ( Orco ) is the most conserved and essential OR gene among these species and RNA interference (RNAi) can decrease their mRNA expression level to <50%. RNAi knockdown rice planthoppers were anosmia and were unable to seek or locate rice plants in behavioral tests. CONCLUSION: The results demonstrate the importance of the planthopper Orco genes in locating rice plants. This information may aid in the development of RNAi‐based transgenic rice and other pest management technologies. © 2018 Society of Chemical Industry